Clinical Impact of CD25/CD123 Coexpression in Adult B-Cell Acute Lymphoblastic Leukemia Patients. (20th May 2020) - Aref, Salah; El Agdar, Mohamed; Khaled, Nada; Ibrahim, Lamyaa; El-Ghonemy, Mohamed S.
Abstract : This study aimed to determine the clinical impact of CD25 + /CD123 + coexpression in adult B-cell acute lymphoblastic leukemia (B-ALL) cases. One hundred and twenty newly diagnosed B-ALL patients (≤60 years old) were included in this study. CD123 and CD25 expression on leukemic blast cells were assessed using flow cytometry. CD25 + /CD123 + coexpression was detected in 40/120 B-ALL patients (33.3%). All B-ALL patients showed CD25 + /CD123 + coexpression had lower induction of remission response and shorter overall survival as compared to B-ALL cases lacking coexpression. In conclusion, CD25 + /CD123 + positive coexpression is a reliable flow cytometry marker for prediction of the outcome of adult B-ALL patients and could be used as a novel parameter for risk stratification of adult B-ALL cases.